Intranasal boosting with MVA encoding secreted mycobacterial proteins Ag85A and ESAT-6 generates strong pulmonary immune responses and protection against M. tuberculosis in mice given BCG as neonates. Issue 12 (19th March 2021) - Khanna, Mayank; Rady, Hamada; Dai, Guixiang; Ramsay, Alistair J.
Highlights: A recombinant poxvirus vaccine encoding Ag85A and ESAT-6 of M. tuberculosis (MVA-AE) was generated. Respiratory boosting with MVA-AE enhanced protection against TB in mice given BCG as neonates. Elevated Th1 and Th17 immunity was seen after MVA-AE boosting in lungs of mice given BCG as neonates. MVA-AE boosting also generated lung CD4 + T cells against ESAT-6, not seen in mice given only BCG. Abstract: Bacille-Calmette-Guerin (BCG) has variable efficacy as an adult tuberculosis (TB) vaccine but can reduce the incidence and severity of TB infection in humans. We have engineered modified vaccinia Ankara (MVA) strain vaccine constructs to express the secreted mycobacterial proteins Ag85A and ESAT-6 (MVA-AE) and evaluated their immunogenicity and protective efficacy as mucosal booster vaccines for BCG given subcutaneously in early life. Intranasal delivery of MVA-AE to young adult mice induced CD4 + and CD8 + T cell responses to both Ag85A and ESAT-6 in lung mucosae. These responses were markedly enhanced in mice that had been primed neonatally with BCG prior to intranasal MVA-AE immunization (BCG/MVA-AE), as evidenced by numbers of pulmonary Ag85A-, ESAT-6-, and PPD-specific CD4 + and CD8 + T cells and by their capacity to secrete multiple antimicrobial factors, including IFNγ, IL-2 and IL-17. Moreover, MVA-AE boosting generated multifunctional lung CD4 + T cells responding to ESAT-6, which were not, as expected, detected in control mice given BCG, and elevated Ag85A-specific circulating antibody responses. After aerosol challenge with M. tuberculosis H37Rv (Mtb), the BCG/MVA-AE group had significantly reduced mycobacterial burden in the lungs, compared with either BCG primed mice boosted with control MVA or mice given only BCG. These data indicate that intranasal delivery of MVA-AE can boost BCG-induced Th1 and Th17-based immunity locally in the lungs and improve the protective efficacy of neonatally-administered BCG against M. tuberculosis infection.